2017
DOI: 10.4067/s0718-090x2017000100007
|View full text |Cite
|
Sign up to set email alerts
|

Hugo Chavez's Polarizing Legacy: Chavismo, Media, and Public Opinion in Argentina's Domestic Politics

Abstract: Since Hugo Chávez Frias assumed the Venezuelan presidency in 1999, Venezuela has strengthened ties with most of its Latin American neighbors, particularly those where sympathetic leftist administrations also managed to assume power, including Argentina. With our analysis we show: 1) that Argentine media, divided between pro-and anti-government positions, presents a polarized view of chavismo; and 2) that Argentine public opinion regarding Chávez is not necessarily divided on the basis of ideological affiliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The resulting polarization pervades Venezuelan political life and even shapes who believes in different political conspiracy theories (Carey 2019). In fact, Chávez even polarized public opinion in places outside of Venezuela (Sagarzazu and Mouron 2017).…”
Section: Political Polarizationmentioning
confidence: 99%
“…The resulting polarization pervades Venezuelan political life and even shapes who believes in different political conspiracy theories (Carey 2019). In fact, Chávez even polarized public opinion in places outside of Venezuela (Sagarzazu and Mouron 2017).…”
Section: Political Polarizationmentioning
confidence: 99%
“…On one hand, studies have shown that Hugo Chávez's image has been used to criticize some progressive policies by leftist administrations (for instance, see: Kitzberger, 2010). On the other hand, Sagarzazu and Mouron (2017) demonstrated that the relationship with Venezuela has successfully polarized the media and public opinion in Argentina along a government-opposition cleavage rather than an ideological one. Nevertheless, none of these studies has answered the question of why this strategy has been used by the right-wing opposition in Latin America, or what its correlates are in public opinion in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The agenda-setting theory also induced other several research directions [2]. One of them focuses on detecting media bias, either by taking into account the number of mentions related to a preferred political party [11,12] or by identifying the ideology through the position of the media regards to certain issues or actors [13,14]. Since the irruption of internet, a quantitative analysis based on the access to big data has become available, as for instance, those who take into account temporal dependence of the media and public attention.…”
Section: Introductionmentioning
confidence: 99%